Design and fabrication of a multi-focusing artificial compound eyes with negative meniscus substrate. (7th March 2017) - Luo, Jiasai; Guo, Yongcai; Wang, Xin; Fan, Fenglian
Abstract: Miniaturized artificial compound eyes with a large field of view (FOV) have potential application in the area of micro-optical-electro-mechanical-system (MOEMS). A new non-uniform microlens array (MLA) on a negative meniscus substrate, fabricated by the melting photoresist method, was proposed in this paper. The multi-focusing MLA reduced the defocus effectively, which was caused by the uniform array on a spherical substrate. Moreover, like most ommatidia in compound eyes, each microlens of the multi-focusing MLA was arranged in one of the eleven concentric circles. In order to match with the multi-focusing MLA and avoid the total reflection, the negative meniscus substrate was fabricated by a homebuilt mold with a micro-hole array and polydimethylsiloxane coelomic compartment attached. The coelomic compartment is capable of offering an excellent injection environment without bubbles and impurities. Due to the direct 3D implementation of the MLA, rich available materials can be used by this method without substrate reshaping. As the molding material, the ultraviolet curing adhesive NOA81 can be cured within ten few seconds under ultraviolet which relieve intensive labor and protect the stereolithography apparatus effectively. The experimental results show that this new MLA has a better imaging performance, higher light usage efficiency and larger FOV because of the negative meniscus and multi-focusing MLA. Moreover, due to the homebuilt mold, more accurate geometrical parameters and shorter processing cycle were realized. Accordingly, together with an appropriate hardware, this MLA has diverse potential applications in medical imaging, military and machine vision.